2013
DOI: 10.4081/rt.2013.e22
|View full text |Cite
|
Sign up to set email alerts
|

Endodermal Sinus Tumor of Vagina in Infants

Abstract: Endodermal sinus tumor (or Yolk Sac tumor) of the vagina is a rare malignant germcell tumor which is seen exclusively in children younger than 3 years of age. We report two cases of endodermal sinus tumor of the vagina. In both cases no radiological investigation was done and serum alpha-fetoprotein was elevated. The histopathological examination of both the tumor masses revealed vaginal endodermal sinus tumor. Periodic-acid-Schiff stain with diastase showed diastase resistant hyaline globules. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Many studies have reported that YST occurs in the vagina, seminal vesicle, pancreas, omentum and stomach, as well as in the intracranial and sacrococcygeal regions (2,3,(16)(17)(18)(19)(20)(21)(22)(23). GCTs originating in the intracranial region almost always occur in the suprasellar regions or pineal gland, but tumors in the cerebellar hemisphere are extremely rare (2).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that YST occurs in the vagina, seminal vesicle, pancreas, omentum and stomach, as well as in the intracranial and sacrococcygeal regions (2,3,(16)(17)(18)(19)(20)(21)(22)(23). GCTs originating in the intracranial region almost always occur in the suprasellar regions or pineal gland, but tumors in the cerebellar hemisphere are extremely rare (2).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation includes a history of bloody vaginal discharge, often accompanied by a polypoid mass protruding from the vagina which was not the case in our patient. Most common differential diagnosis is botyroides sarcoma differentiated by its characteristic grape like appearance and histopathology [ 4 ]. The use of serum AFP as tumor marker has been well established for patients with YST.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal yolk sac tumors occur mostly in children under 3 years of age. 13 The main symptoms are irregular vaginal bleeding and occasional tumor shedding from the vagina, accompanied by a significant increase in AFP. The sensitivity of vaginoscopy under anesthesia is 100% 14 ; therefore, for children with vaginal bleeding who are suspected of having vaginal tumors, vaginoscopy under anesthesia is recommended.…”
Section: Vaginal Neoplasmsmentioning
confidence: 99%